Rickettsial Infections and Fever, Vientiane, Laos - Simaly Phongmany (Emerging Infectious Diseases, 2006)
Rickettsial diseases have not been described previously from Laos, but in a prospective study, acute rickettsial infection was identified as the cause of fever in 115 (27%) of 427 adults with negative blood cultures admitted to Mahosot Hospital in Vientiane, Laos. The organisms identified by serologic analysis were Orientia tsutsugamushi (14.8%), Rickettsia typhi (9.6%), and spotted fever group rickettsia (2.6% [8 R. helvetica, 1 R. felis, 1 R. conorii subsp. indica, and 1 Rickettsia "AT1"]). Patients with murine typhus had a lower frequency of peripheral lymphadenopathy than those with scrub typhus (3% vs. 46%, p<0.001). Rickettsioses are an underrecognized cause of undifferentiated febrile illnesses among adults in Laos. This finding has implications for the local empiric treatment of fever.